2009
DOI: 10.2174/1567270000906010065
|View full text |Cite
|
Sign up to set email alerts
|

The Renin-Angiotensin-Aldosterone System as a Therapeutic Target for Endothelial Dysfunction

Abstract: Endothelial dysfunction has been characterized by decreased nitric oxide (NO) synthesis or reduced NO bioavailability, which relates to inflammation, proliferation of smooth muscle cells, deposition of extracellular matrix, vasoconstriction, and a prothrombotic state within the vessel lumen. The endothelium is the site of the final step of synthesis of both NO and angiotensin II (Ang II) and is a major site for their countervailing interaction. Evidence suggests that renin-angiotensin system (RAS) blockade may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 109 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…Nitrite reductase-like protein may contribute to ACE inhibitory activity through the interaction between the NO pathway and RAAS via vascular (endothelial) dysfunction mechanisms [41]. However, there is as yet no supporting data for our hypothesis asserting the synergistic effect of nitrite reductase as an ACE inhibitor.…”
mentioning
confidence: 69%
“…Nitrite reductase-like protein may contribute to ACE inhibitory activity through the interaction between the NO pathway and RAAS via vascular (endothelial) dysfunction mechanisms [41]. However, there is as yet no supporting data for our hypothesis asserting the synergistic effect of nitrite reductase as an ACE inhibitor.…”
mentioning
confidence: 69%
“…The existence of brain renin-angiotensin system (RAS) has been reported previously, and it has been found to be involved in the modulation of cardiovascular and fluid-electrolyte homeostasis, as well as other brain-specific function. Evidence suggested that RAS blockade may have an impact on early mechanisms of vascular disease, such as endothelial dysfunction and vascular remodeling that underlie clinical manifestations of cardiovascular disease [ 6 ]. As a predominate bioactive peptide in RAS, Angiotensin II (AngII) has been suggested to be a significant contributor to the pathophysiology of ischemic stroke [ 7 9 ], which, after acting on its receptor (AngII type 1 receptor, AT 1 R; AngII type 2 receptor, AT 2 R ), can activate a series of cell signaling pathways, including phosphatidyl inositol (PI) signaling pathways that associated with vasoconstrictor function of Ang II.…”
Section: Introductionmentioning
confidence: 99%